Предмет: Математика,
автор: togu2332
помогите пожалуйста упростить выражение
a) 3x + 6 - 2x=
б) 3у - 2 + 6у + 7=
в) -у - аb + 4y - 5ab=
г) 8x - 4(2x - 5)=
Ответы
Автор ответа:
1
Ответ: а) 3х+6-2х=3х-2х+6=х+6
б)3у-2+6у+7=3у+6у-2+7=9у+5
в)-у-ab+4y-5ab=-y+4y-ab-5ab=3y-6ab
г) 8х-4(2х-5)=8х-8х+20=20
Пошаговое объяснение:
Похожие вопросы
Предмет: Русский язык,
автор: диди36
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: angelan2
Предмет: Математика,
автор: kikomi
Предмет: Алгебра,
автор: samslime1337